Comparative Outcomes of V-Y Advancement Flap Versus Full-Thickness Skin Grafting in Frontotemporal Reconstruction: Aesthetic and Functional Assessment Using FACE-Q Questionnaire - Yavuz, Ersin; Ercan, Alp (Cerrahpaşa Medical Journal, 2025)
Objective: Frontotemporal reconstruction after malignant tumor excision poses aesthetic and functional challenges due to the region’s complex anatomy and visibility. This study aimed to compare outcomes of V-Y advancement flaps vs. full-thickness skin grafts in moderate midtemporal defects. Methods: A retrospective review was conducted on patients who underwent excision of squamous cell carcinoma or malignant melanoma. Defects were reconstructed with either V-Y advancement flaps or fullthickness skin grafts. Aesthetic outcomes were assessed 1 year postoperatively using the FACE-Q Aesthetic Module, evaluated by patients, a plastic surgeon, and a non-plastic specialist. Results: A total of 14 patients (7 V-Y advancement flap, 7 full-thickness skin graft) were included. The V-Y flap group showed significantly higher FACE-Q scores for skin texture, color match, and facial expression, especially within the “facial expression and emotional state” domain. No significant difference was found in the “psychological function” domain. The V-Y technique preserved regional mobility, avoided donor site morbidity, and minimized risk to the frontal branch of the facial nerve. No complications or recurrences were reported. Conclusion: V-Y advancement flaps offer a safe, effective, and aesthetically superior option for selected frontotemporal defects, especially when patient emotional expressiveness and facial harmony are critical. They may be preferred over skin grafts in appropriately selected cases. Cite this article as: Yavuz E, Ercan A. Comparative outcomes of V-Y advancement flap versus full-thickness skin grafting in frontotemporal reconstruction: aesthetic and functional assessment using FACE-Q questionnaire. Cerrahpaşa Med J. 2025, 49, 0056, doi:10.5152/cjm.2025.25056